2006
DOI: 10.1590/s0066-782x2006000500012
|View full text |Cite
|
Sign up to set email alerts
|

Terapia celular na cardiomiopatia dilatada

Abstract: A forty-one-year-old male with systolic heart failure, FC-III NYHA, clinical stage C due to dilated cardiomyopathy was submitted to an autologous transplant of the mononuclear fraction of bone marrow via coronary artery system through heart catheterism. Two months after the procedure, there was a decrease in plasma BNP and cardiac area reduction at the thorax X-ray and nuclear magnetic resonance. The echocardiogram showed decrease of the secondary regurgitation and mitral ring dilatation. There was a better pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…Baseado nestes dados e na experiência adquirida nos pacientes chagásicos crônicos, iniciou-se no Brasil um ensaio clínico de fase I com pacientes com CMP dilatada. Martino et al 29 relataram o primeiro caso de terapia em humanos, com injeção de células por via intracoronariana. O ensaio coordenado por Martino et al já incluiu trinta pacientes, dos quais 24 com injeção intracoronariana e cinco com injeção intramiocárdica.…”
Section: Cardiomiopatia Dilatadaunclassified
“…Baseado nestes dados e na experiência adquirida nos pacientes chagásicos crônicos, iniciou-se no Brasil um ensaio clínico de fase I com pacientes com CMP dilatada. Martino et al 29 relataram o primeiro caso de terapia em humanos, com injeção de células por via intracoronariana. O ensaio coordenado por Martino et al já incluiu trinta pacientes, dos quais 24 com injeção intracoronariana e cinco com injeção intramiocárdica.…”
Section: Cardiomiopatia Dilatadaunclassified
“…The first study using the mononuclear fraction appeared in cardiology and showed promising results, encouraging the use of these cells as a treatment in other clinical situations (Guarita‐Souza et al, 2005; Martino et al, 2006). Caldas et al (2008 studied the utilization of mononuclear and mesenchymal cells in a renal failure model using Wistar rats.…”
Section: Introductionmentioning
confidence: 99%